Aplikasi Pengelolaan Barang Reject Menggunakan Delphi 2010 dan MySQL di PT. Dream Sentosa Indonesia - Indra Nanda; Nita (LP2M CBI PRESS, 2016)
Dream Sentosa Indonesia (DSI) is a Foreign Investment Company (PMA) engaged in the Bags and Garment industry with its head office at 444 Dunchon 2- Dong Gangdong-gu, 134-822 Seoul, Korea. The garment manufacturing process factory is located in Karawang, Indonesia. It was found that the process of managing reject goods, the process of making reports, the recording process, and the storage process were still not optimal. This makes it difficult for employees to search for data. A process for managing reject goods is required, which can make reports and data recording processes more neat and well structured, as well as a computerized data storage process to facilitate the process of searching for data. This application is expected to help fix all the shortcomings of the existing system into a better system. The reject goods management application has a very important role in building and developing a reject goods data information system at PT. Dream Sentosa Indonesia. The design system in making the rejected item data application was developed using several software namely Borland Delphi10, XAMPP which is a combination of Apache Web Server, PHP and MYSQL. By using the Borland Delphi10 program, it can provide convenience in managing reject goods data.